An Overview of Ebola Virus Disease (Community Based Medical Journal, 2016)
Ebola virus is an aggressive pathogen that causes a highly lethal hemorrhagic fever syndrome in humans and nonhuman primates. Ebola Virus Disease (EVD) is characterized by the sudden onset of fever and malaise accompanied by other nonspecific signs and symptoms such as myalgia, headache, vomiting, and diarrhea. Among EVD patients, 30%-50% experience hemorrhagic symptoms. In severe and fatal forms, multi organ dysfunction including hepatic damage, renal failure, and central nervous system involvement occur, leading to shock and death. The wildlife reservoir has not been definitively ascertained; however evidence supports fruit bats as one reservoir. The virus initially spreads to the human population after contact with infected wildlife and is then spread person-to-person through direct contact with body fluids. The incubation period is 2-21 days. Prevention includes decreasing the spread of disease from infected animals humans. Properly cooking meat and wearing protective clothing when handling meat may also be helpful. Samples of bodily fluids and tissues from people with the disease should be handled with special caution. There is currently no antiviral therapy or vaccine that is effective against Ebola virus infection in humans. Efforts to help those who are infected are supportive and include giving either oral rehydration therapy or intravenous fluids. The disease has a high risk of death, mortality between 50% and 90% of those infected with the virus.CBMJ 2016 January: Vol. 05 No. 01 P: 50-54